IEM wins bid to host ITA-AITES World Tunnel Congress 2020 and 46th general assembly in Kuala Lumpur - Ooi, Taik Aun, Ir. Dr (The Institution of Engineers, Malaysia (IEM), 2017)
Link to publisher’s homepage at http://www.myiem.org